Mitogenome of Gymnothorax minor and phylogenetic relationship with its congeners and related genera (Anguilliformes: Muraenidae) - Song, Sze-Looi; Yong, Hoi-Sen; Loh, Kar-Hoe; Lim, Phaik-Eem; Yee, Amy Hui Then; Praphathip Eamsobhana, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Gymnothorax minor is a moray eel of the family Muraenidae found in the Western Pacific Ocean. We report here its complete mitogenome as determined by Illumina next-generation sequencing and the phylogenetic relationship with its congeners and other taxa of the family Muraenidae. The whole mitogenome of G. minor had a total length of 16,574 bp, comprising 37 genes - 13 protein-coding genes (PCGs), two ribosomal ribonucleic acid (rRNA) and 22 transfer ribonucleic acid (tRNA) genes - and a control region. Excepting cox1 with GTG, the other 12 PCGs had ATG start codon. Seven of its PCGs had incomplete stop codon - five (nad2; cox1; cox2; nad3 and nad4) with T and two (atp6 and cox3) with TA. Molecular phylogeny based on 13 PCGs was concordant with 15 mitochondrial genes (13 PCGs and 2 rRNA genes). The subfamily Muraeninae as well as the subfamily Uropterygiinae were monophyletic. However, the genus Gymnothorax was paraphyletic, with G. minor forming a sister group with Rhinomuraena quaesita in the lineage containing also G. kidako and G. formosus forming a sister group with Enchelynassa canina. The phylogenetic relationship of the genus Gymnothorax and related taxa of the family Muraenidae, based on the mitochondrial cob gene, was in general similar to that based on 15 mt-genes. The mitogenome is useful for future studies on phylogenetics and systematics of eels of the family Muraenidae and other taxa of the order Anguilliformes.